Emergence of training and development in organisations – A historical perspective - Manodip Ray Chaudhuri; Mahima Roy; Nandita Mehrotra; Pragya Talukdar (New Applied Studies in Management, Economics & Accounting, 2022)
Employee development and training programmes are essential to the global success of firms. These programmes help organisations raise employee productivity and promote corporate culture while also allowing employees to expand their skills. These training programmes, while necessary for the survival of today's enterprises, were not part of the organization's culture from the start. Training as a concept did not arise until the late 1930s. Training became a notion during World War II, when the US government cooperated with the country's industries to train workers in order to increase the production of military hardware. Following the war, several businesses began providing classroom and on-the-job training to their employees in order to improve their overall efficiency. The ISD model was used to design the trainings. Becker's Theory on Human Capital clarified that training should be viewed as an investment rather than a cost to the organisation. Because of the increasingly complex nature of work and developments in instructional technology, the major site of training has shifted away from the classroom to videos and simulation. Training programmes are no longer planned separately from an employee's job, but are rather integrated into the work process, allowing individuals to grow while they work. Employee training has become more interactive owing to the use of Artificial Intelligence, Virtual Reality, and Machine Learning. Trainees can now experiment and judge the implications of their actions in real-life scenarios. These technology improvements have benefited both individuals and businesses because these tools provide real-time feedback to employees, allowing them to take prompt action and correct problems. Training & Development programmes have progressed from being an organization's initiative to becoming a vital element of the organization's strategy, and will continue to progress in the future, providing a variety of benefits to the organisations.